The Ocean System Pathways (OSPs): A New Scenario and Simulation Framework to Investigate the Future of the World Fisheries - O. Maury; D. P. Tittensor; T. D. Eddy; E. H. Allison; T. Bahri; N. Barrier; L. Campling; W. W. L. Cheung; K. Frieler; E. A. Fulton; P. Guillotreau; R. F. Heneghan; et al. (Earth's Future)
Abstract The Fisheries and Marine Ecosystems Model Intercomparison Project (FishMIP) has dedicated a decade to unraveling the future impacts of climate change on marine animal biomass. FishMIP is now preparing a new simulation protocol to assess the combined effects of both climate and socio‐economic changes on marine fisheries and ecosystems. This protocol will be based on the Ocean System Pathways (OSPs), a new set of socio‐economic scenarios derived from the Shared Socioeconomic Pathways (SSPs) widely used by the Intergovernmental Panel on Climate Change (IPCC). The OSPs extend the SSPs to the economic, governance, management and socio‐cultural contexts of large pelagic, small pelagic, benthic‐demersal and emerging fisheries, as well as mariculture. Comprising qualitative storylines, quantitative model driver pathways and a “plug‐in‐model” framework, the OSPs will enable a heterogeneous suite of ecosystem models to simulate fisheries dynamics in a standardised way. This paper introduces this OSP framework and the simulation protocol that FishMIP will implement to explore future ocean social‐ecological systems holistically, with a focus on critical issues such as climate justice, global food security, equitable fisheries, aquaculture development, fisheries management, and biodiversity conservation. Ultimately, the OSP framework is tailored to contribute to the synthesis work of the IPCC. It also aims to inform ongoing policy processes within the United Nations Food and Agriculture Organization (FAO). Finally, it seeks to support the synthesis work of the Intergovernmental Science‐Policy Platform on Biodiversity and Ecosystem Services (IPBES), with a particular focus on studying pathways relevant for the United Nations Convention on Biological Diversity.